REVITALISASI MAKNA GURU DARI AJARAN TASAWUF DALAM KERANGKA PEMBENTUKAN KARAKTER - Irham, Irham; Basith, Yudril (ULUL ALBAB Jurnal Studi Islam, 2018)
This article seeks to describe the meaning of teachers based on the teachings of Sufism that can be a reference to revitalize the important role of educators in order to build character. It uses the perspective of Sufism since this teaching focuses on pupil’s moral development both outwardly and inwardly. The purpose of this article is to adapt the meaning of teacher in islamic mysticism perspective into the meaning of teacher in general for character education. It employs literary study by referring to the thoughts of figures or scholars of islamic mysticism and supported by the theory outside the study of islamic mysticism, then formulated into a conceptual construct of this article. The conclusion shows that the teacher in Sufism with his qualifications has the task of educating pupil’s moral that is not limited in a certain space and time. Teacher builds closeness with the pupils from the inner and outer sides. They are treated like a teacher treating himself. Teacher in this sense is as role model, counselor, director, advisor, to shape pupil’s moral. This meaning can improve the weaknesses of the modern education theory, which generally interprets teacher as facilitator, mediator, or as teachers (transfer of knowledge/transfer of values), which has not touched on pupil’s inner side.